Youth Inequality of Opportunities in the Labour Market: Evidence from West African Countries - Sanoussi, Yacobou; Golo, Yao Nukunu; Wonyra, Kwami Ossadzifo (American Journal of Social Sciences and Humanities, 2019)
The objective of this paper is to estimate the opportunity inequalities of youth labor market access and the factors influencing this access, using data from School to Work Transition Survey (SWTS) in Benin, Liberia, and Togo. To achieve the objectives of this paper, we compute the Human Opportunity Index (HOI) using three indicators of access to youth labour market. The inequality of opportunity is much more pronounced in Benin for job opportunities (33.6), contract (40.8) and Liberia for the job opportunity with insurance (49.3). We note that parental characteristics contribute more to the inequality of opportunity in accessing a job in Togo compared to other countries. We also find that demographic factors contribute much more to the inequality in access to employment in Liberia (78.02%) compared to Benin (74.26%) and Togo (45.05%). The average coverage and access rates reveal that more effort is needed to ensuring equitable youth labor market access in these countries.